Perception, Action, and Cognition - Snehlata Jaswal (Frontiers Media SA, 2016)
Even as simple a task as quenching thirst with a glass of water involves a sequence of perceptions and actions woven together by expectations and experience. What are the myriad links between perception and action, and what does cognition have to do with them? Intuitively we think that perception precedes action, but we also know that action moulds perception. The reciprocal links between perception and action are now accepted almost universally. The discovery of mirror neurons that encode observed actions has further emphasized the coupling of perception and action. The real aim of this research topic is to go beyond identifying the evidence for perception-action coupling, and study the cognitive entities and processes that influence the perception-action link. For example, the internal representations of perceived and produced events are created and modified through experience. Yet the perception action link is considered relatively automatic. To what extent is the perception-action link affected by representations and their manipulations by cognitive processes? Does selective attention modify the perception action coupling? How, and to what extent, does the context provide sources of cognitive control? The developmental trajectory of the perception-action link and the influence of cognition at various stages of development could be another line of important evidence. The responses to these and other such questions contribute to our understanding of this research area with significant implications for perception-action coupling.
English
Keywords: Mirror mechanisms; Perception; action; Embodied Cognition; Cognition; Perception-Action Coupling; theory of event coding